Kepadatan Siput Gonggong (Strombus turturella) dengan Faktor Lingkungan Di Perairan Teluk Kelabat Kepulauan Bangka Belitung - Rika Fifiyanti; Okto Supratman; Eva Utami; Okto Supratman (Universitas Bangka Belitung, 2020)
Dog conch (Strombus turturella) is an important fishery commodity in the Bangka Belitung Islands. The population is declining due to overexploitation and habitat destruction. This study aims to analyze the density of the distribution pattern and the relationship between the density of the Dog conch (Strombus turturella) with environmental factors in the waters of Klabat Bay. The study was conducted in April 2019 in the waters of Klabat Bay, Bangka Belitung Islands Province. Sampling was carried out at five stations using a square measuring 1x1 meter, the average density of Dog conch at the study site was 9,460 ind/ha. The highest density is found in station 2 with a density of 15,600 Ind/ha, while the lowest density is at station 4 with a value of 3,300 Ind/ha. The distribution pattern of the Dog conch at each location there are differences, namely the grouping and uniform distribution patterns. Dog conch in the study site were related to sand substrate type, low organic matter and overgrown with seagrass with low cover and density. Seagrass species found were small, Halophila minor and Halodule uninervis.